Quality Leadership and Management, Technology-Based Instruction, Work Attitude and Teachers’ Performance in the New Normal - Jimeno, Jiesrel B.; Prado, Nenita I (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
The study is a causal model development of the quality leadership and management level, technology-based Instruction, and work attitude on teachers' performance in the new normal. The descriptive–correlational, causal–comparative research design was employed using a modified researcher survey instrument. It was conducted in Bangkok Metropolitan Region, Bangkok, Thailand, with Adventist Filipino teachers. The data collected from the questionnaires and Google forms were examined and interpreted using the frequency count and percent, mean and standard deviation, Pearson Product - Moment Correlation, multiple regression, and path analysis. The quality leadership and management level indicated that Adventist Filipino teachers have a good working relationship with the school director/Department head/Coordinator and their co-teachers. Adventist Filipino Teachers have a very high positive attitude to technology and use it for Instruction. Teachers' work attitude indicates a high good character in all sub-variables. The Adventist Filipino teachers' performance is outstanding and commendable. A positive relationship exists between teachers' performance and quality leadership management, technology-based Instruction, and work attitude. The best-fitting model is anchored on quality leadership, management, and teacher work attitude.